Analysis of the world’s systems of environmentalism and strategic development of the ecological and economic system of Ukraine - Shara, Svitlana (Technology audit and production reserves, 2023)
The object of research is economic theories and modern ecological and economic systems. The evolution of economic theories in each historical period of the development of social relations has been analyzed and the main economic schools that most accurately described the existing economic systems have been identified. The work solved the problem of strategic development of the economic system of Ukraine based on the author’s vision of the evolution of economic theories in the dynamics of development and their historicism, modern economic theory and the peculiarities of the development of certain scientific directions. Analysis of the development of economic systems indicates a logical sequence of development towards institutionalism, historicism and environmentalism. The author’s own developments of the structural-logical scheme of the evolution of economic theories and economic theories of modernity, the institutional economic system and the structural-logical scheme of the environmental economy are given. Special attention is paid to the ecological revolution, the theory of V. I. Vernadsky and environmental aspects. The obtained results determine that the development of Ukraine should be based on environmental principles, environmental sociology, ecophilosophy and ecoethics. This is determined by the limitation of natural resources and the need for rational use and revitalization of territories and individual elements of the biosphere complex that suffered as a result of military aggression. Taking into account the significant geopolitical natural resource potential of Ukraine, ways of multiplication through the formation of an environmental institutional economy integrated into the European economic and ecological integral space are determined. The importance of water resources of Ukraine and the role of organic farming in the revitalization processes of the Dnipro basin are highlighted. Identified proposals for the formation of environmental sustainability of the economy and the socio-economic system, both in general and for individual natural-resource components. Special attention is paid to the systematic strategic management of the development of land resources and land-resource potential. This is possible if corruption is eliminated and the economy exits from the economic underground.